(untitled) (International Journal of Engineering Materials and Manufacture, 2021)
Solid waste is an inevitable by-product of human beings, animals and also of industrial-commercial activities. Obviously solid waste creates a greater problem to the environment, if it is not properly managed. Bangladesh being a heavily populated country needs to pay adequate attention to waste management. Waste generation in Bangladesh is increasing because of rapid urbanization and economic development of the country. At present, total solid waste generation in Bangladesh is around 27000 tons/day and in the four important city corporations is about 13,332 tons. Particularly in Dhaka city, it is around 7500 tons/day. This amount is likely to reach about 47000 tons per day in entire Bangladesh and 15000 tons per day for Dhaka city alone by 2030. At present, landfilling is the only method for disposal of heterogeneous waste stream and there are three landfills in Dhaka City. Most of these landfill sites are in open dumps polluting land, water and air. Development of any new landfill site is near to impossible due to land scarcity and increasing of land prices especially in Dhaka City. Improperly disposed waste is posing serious health implications to the people and it may transmit various diseases especially by non-degradable wastes like polythene. Rather, a proper Segregation system to recover of resource from plastic wastes can play a very important role in mitigating the difficulties of solid waste that can act as a raw material for product design in Bangladesh too. Therefore, a comprehensive study report followed by a model of plastic waste segregation system for Bangladesh has been highlighted in the paper.